Gambaran Perilaku Sehat Pada Siswa di SMA Muhammadiyah 1 Surakarta Tahun 2015 - Rumshita, Arsy; , Siti Arifah, S.Kp.,M.Kes; , Ambarwati, S.Pd.,M.Si (2016)
Adolescence is a period of transition from childhood to adulthood. In adolescence, this has a very complex issue, along with a natural transition in adolescence. Therefore, the teenager as the nation's next human need to be prepared to be healthy physically, spiritually, mentally and spiritually. This study aimed to describe the healthy behavior in students at SMA Muhammadiyah 1 Surakarta. This type of research is descriptive, using cross sectional approach dilksanakan on July 14 and July 15, 2015 in High School I Surakarta Muhammadiyah. Total population is used throughout the class X and XI in SMA Muhammadiyah 1 Surakarta totaling 498 students. The sampling technique with proportional random sampling, to obtain a sample of 84 respondents. The results showed that the image of healthy behaviors in students of SMA Muhammadiyah 1 Surakarta overall good, with healthy behaviors in students covering a total of 77 respondents (91.7%) did not smoke, 81 respondents (96.4%) did not consume alcohol, 84 respondents ( 100%) have never engage in premarital sex, and as many as 71 respondents (84.5%) of physical activity drive safely. Keywords: smoke behavior, consume alcohol, premarital sex, and activity drive, High School Students